Embeddings - Potts Jason (Cultural Science)
I argue here that the concept of embedding (understood in the mathematical and computer science sense) provides a general way of understanding the relation between generative AI, written language and semiotics, and animal cognition when understood recursively. I propose this framing as an application of cultural science and suggest that this offers a new way to understand the alignment problem between humans and increasingly intelligent machines.